Relationships among soil properties, plant nutrition and arbuscular mycorrhizal fungi-plant symbioses in a temperate grassland along hydrologic, saline and sodic gradients - García, Ileana Vanesa (2008)
Temporal variations in the relationships among plant nutrient concentrations, soil properties and arbuscular-mycorrhizal (AM) fungal dynamics were studied along a topographic and saline gradient in a temperate grassland soil. Soil and plant (Lotus tenuis, Paspalum vaginatum, Stenotaphrum secundatum) samples were collected on four seasonally based occasions. The morphology of AM root colonization had a similar pattern in the plants studied. Maximum arbuscular colonization occurred at the beginning of the growing season in late winter and was minimal in late summer, but maximal vesicular colonization occurred in summer and was minimal in winter, suggesting a preferential production of these morphological phases by the fungus with respect to season. The greatest arbuscular colonization was associated with the highest N and P concentrations in plant tissue, suggesting a correspondence with increases in the rate of nutrient transfer between the symbiotic partners. Water content, salinity and sodicity in soil were positively associated with AM root colonization and arbuscule colonization in L. tenuis, but negatively so in the grasses. There were distinct seasonally related effects with respect to both spore density and AM colonization, which were independent of particular combinations of plant species and soil sites.